1988
DOI: 10.1136/ard.47.9.759
|View full text |Cite
|
Sign up to set email alerts
|

Screening for proteinuria in a rheumatology clinic: comparison of dipstick testing, 24 hour urine quantitative protein, and protein/creatinine ratio in random urine samples.

Abstract: GlasgowSUMMARY Measurements of protein/creatinine ratio in 'spot' urine samples were compared with measurements of 24 hour quantitative proteinuria and side room 'dipstick' testing in 104 samples from 90 patients presenting consecutively to a rheumatology unit. Linear regression analysis showed a highly significant correlation between the random urinary protein/creatinine ratio and total protein excretion in 24 hour urine samples (r=0.92, p<0.001, y=6-55x+0-04). Although an approximation of 24 hour urinary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 6 publications
2
28
0
2
Order By: Relevance
“…However, many studies have reported a poor correlation between the dipstick examination and the 24-hour urine assay with high false-positive or false-negative rates. 11,12 We aimed to find a urine protein in preeclampsia that closely correlated with the 24-hour urine protein and was at a Abstract-Early diagnosis and treatment of preeclampsia are essential for prevention of seizure development and fetus maturation. Although various methods have been developed for predicting or monitoring the onset of preeclampsia, a simple assay that can be used as a home or point of care test remains unavailable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies have reported a poor correlation between the dipstick examination and the 24-hour urine assay with high false-positive or false-negative rates. 11,12 We aimed to find a urine protein in preeclampsia that closely correlated with the 24-hour urine protein and was at a Abstract-Early diagnosis and treatment of preeclampsia are essential for prevention of seizure development and fetus maturation. Although various methods have been developed for predicting or monitoring the onset of preeclampsia, a simple assay that can be used as a home or point of care test remains unavailable.…”
mentioning
confidence: 99%
“…However, many studies have reported a poor correlation between the dipstick examination and the 24-hour urine assay with high false-positive or false-negative rates. 11,12 We aimed to find a urine protein in preeclampsia that closely correlated with the 24-hour urine protein and was at a concentration range allowing the development of a rapid laminar flow immunoassay. This rapid test should be sensitive and specific for the preeclampsia diagnosis and can be easily used by both patients and healthcare providers.…”
mentioning
confidence: 99%
“…A methodological limitation of our study is that at the baseline examination, performed more than 20 years ago, we measured total urinary protein concentration from spot urine samples with the Coomassie brilliant blue method, instead of using a specific assay for albumin [46][47][48] which constitutes about one-half of total urinary protein [49]. Correlation of albuminuria with proteinuria has been previously documented with convergence toward the line of unity with increasing degrees of proteinuria [50].…”
Section: Discussionmentioning
confidence: 99%
“…10 Screening for proteinuria is a common requirement in rheumatological practice, particularly in patients who are receiving second-line drugs. 11 The use of the urine protein:creatinine ratio rather than the 24-h excretion was also of practical value in monitoring the effects of drug therapy in this group of patients. Collection of a random, rather than a 24-h, urine is more convenient and avoids errors due to incomplete urine collection.…”
Section: Discussionmentioning
confidence: 99%